Export of Wildlife and Products from Calcutta Port - an Indepth Study - Chakrabarti, Kalyan (Indian Forester, 1992)
Like any other activity export of wildlife and products also had seasonal and cyclic fluctuations. There are booms and slumps in export activities as well. The analysis of export statistics on wildlife and products clearly indicates that the export activity was at its peak during 1977 both in respect of value and quantity except for live birds, live mammals, snake skins and turtle/tortoise shells in which cases the peak year was 1976. The significant export activity also persisted during 1978 though with diminishing amplitude. But since 1979 there was a sharp fall in export activity and then year after year export is getting drastically reduced. This is primarily because of various restrictions imposed for export on wildlife and products by the authorities. The export data collected during the years 1975 to 1988 from Calcutta Port are presented in this paper. It includes the data on export by air, sea and postal parcels. The analysis of the data brings out revealing facts on different components of export. Japan stands out as the main country of import in respect of live birds over the period under study and is followed by countries like Holland, West Germany, Hongkong, Taiwan, Singapore, France etc. Another important dimension in export activity is the signing of an international convention namely Convention of International Trade on Endangered Species (CITES). India became member of CITES since October 18, 1976. This international convention has greatly effected an international control on export trade on wildlife and its products and paved the way for successful wildlife conservation.